Reclaiming fame and glory of the Muslim world - Abdul Razak, Mohd. Abbas (New Straits Times Press (NSTP), 2015)
DURING the Golden Age of Islam (750-1258), Muslims were in the forefront in conquering knowledge through scientific research, exploration and expeditions. In their pursuit of mastering new knowledge and technology, Muslims were prepared and open to the idea of learning all that is positive from the earlier civilisations. As such, they borrowed ideas from the Indians, Persians and Greeks as a way of enriching their own civilisation. Adopt, adapt and assimilate or integrate was the approach used by early Muslim scholars in taking knowledge from those outside the Islamic faith. This meticulous and selective approach in taking ideas from others and adapting those ideas without contradicting the Islamic metaphysical framework (aqa’id) in a way enriched the Islamic civilisation. At the zenith of the Islamic civilisation, Muslim scholars became great authorities in the areas of medicine, philosophy, mathematics, chemistry, astronomy, botany, physical and social sciences. The booming scientific research and exploration works that took place in the many centres in the Middle East attracted Europeans to learn from the Muslims.